The landscape of common genetic drivers and DNA methylation in low‐grade (epilepsy‐associated) neuroepithelial tumors: A review. Issue 6 (17th July 2022) - Jesus‐Ribeiro, Joana; Rebelo, Olinda; Ribeiro, Ilda Patrícia; Pires, Luís Miguel; Melo, João Daniel; Sales, Francisco; Santana, Isabel; Freire, António; Melo, Joana Barbosa
Abstract : Low‐grade neuroepithelial tumors (LNETs) represent an important group of central nervous system neoplasms, some of which may be associated to epilepsy. The concept of long‐term epilepsy‐associated tumors (LEATs) includes a heterogenous group of low‐grade, cortically based tumors, associated to drug‐resistant epilepsy, often requiring surgical treatment. LEATs entities can sometimes be poorly discriminated by histological features, precluding a confident classification in the absence of additional diagnostic tools. This study aimed to provide an updated review on the genomic findings and DNA methylation profiling advances in LNETs, including histological entities of LEATs. A comprehensive search strategy was conducted on PubMed, Embase, and Web of Science Core Collection. High‐quality peer‐reviewed original manuscripts and review articles with full‐text in English, published between 2003 and 2022, were included. Results were screened based on titles and abstracts to determine suitability for inclusion, and when addressed the topic of the review was screened by full‐text reading. Data extraction was performed through a qualitative content analysis approach. Most LNETs appear to be driven mainly by a single genomic abnormality and respective affected signaling pathway, including BRAF p.V600E mutations in ganglioglioma, FGFR1 abnormalities in dysembryoplastic neuroepithelial tumor, MYB alterations in angiocentric glioma, BRAF fusions in pilocytic astrocytoma, PRKCA fusions in papillary glioneuronal tumor, between others. However, these molecular alterations are not exclusive, with some overlap amongst different tumor histologies. Also, clustering analysis of DNA methylation profiles allowed the identification of biologically similar molecular groups that sometimes transcend conventional histopathological classification. The exciting developments on the molecular basis of these tumors reinforce the importance of an integrative histopathological and (epi)genetic classification, which can be translated into precision medicine approaches.